Development of Constructivistic Economic Learning Tools with Advance Organizer - Muhammad Yored; Rufii; Harwanto (Institute of Computer Science (IOCS), 2022)
The purpose of this development is this development is to produce a Constructivistic Economics Learning Tool with an Advance Organizer. The development model used is the Borg & Gall model. The stages of development research on the Borg & Gall model consist of ten steps, namely: (a) research and data collection, (b) planning, (c) initial product development, (d) initial product trial/limited trial, (e ) improvement of the initial product, (f) wider field trial, (g) improvement of the product resulting from wider field test, (h) final product trial, (i) revision or refinement of the final product, (j) dissemination and implementation. The development process involves subject matter experts, instructional design experts and learning media experts to provide feedback and suggestions for improvement. The results of this development research are the Constructivistic Economics Learning Tool Product with Advance Organizer has a material feasibility level of 93.33%, learning design feasibility 91.43%, and learning media feasibility 94.29%. While the small group trial rate is 90.69% and based on field trials 91.07% with very feasible qualifications and does not need to be revised.